Transcutaneous PCO2 for Exercise Gas Exchange Efficiency in Chronic Obstructive Pulmonary Disease. (1st December 2020) - Cao, Min; Stringer, William W.; Corey, Susan; Orogian, Arin; Cao, Robert; Calmelat, Robert; Lin, Fang; Casaburi, Richard; Rossiter, Harry B.; Porszasz, Janos
Abstract: Gas exchange inefficiency and dynamic hyperinflation contributes to exercise limitation in chronic obstructive pulmonary disease (COPD). It is also characterized by an elevated fraction of physiological dead space (VD /VT ). Noninvasive methods for accurate VD /VT assessment during exercise in patients are lacking. The current study sought to compare transcutaneous PCO2 (TcPCO2 ) with the gold standard—arterial PCO2 (PaCO2 )—and other available methods (end tidal CO2 and the Jones equation) for estimating VD /VT during incremental exercise in COPD. Ten COPD patients completed a symptom limited incremental cycle exercise. TcPCO2 was measured by a heated electrode on the ear-lobe. Radial artery blood was collected at rest, during unloaded cycling (UL) and every minute during exercise and recovery. Ventilation and gas exchange were measured breath-by-breath. Bland-Altman analysis examined agreement of PCO2 and VD /VT calculated using PaCO2, TcPCO2, end-tidal PCO2 (PET CO2 ) and estimated PaCO2 by the Jones equation (PaCO2 -Jones). Lin's Concordance Correlation Coefficient (CCC) was assessed. 114 measurements were obtained from the 10 COPD subjects. The bias between TcPCO2 and PaCO2 was 0.86 mmHg with upper and lower limit of agreement ranging −2.28 mmHg to 3.99 mmHg. Correlation between TcPCO2 and PaCO2 during rest and exercise was r 2 =0.907 ( p < 0.001; CCC = 0.941) and VD /VT using TcPCO2 vs. PaCO2 was r 2 =0.958 ( p < 0.0001; CCC = 0.967). Correlation between PaCO2 -Jones and PET CO2 vs. PaCO2 were r 2 =0.755, 0.755, ( p < 0.001; CCC = 0.832, 0.718) and for VD /VT calculation (r 2 =0.793, 0.610; p < 0.0001; CCC = 0.760, 0.448), respectively. The results support the accuracy of TcPCO2 to reflect PaCO2 and calculate VD /VT during rest and exercise, but not in recovery, in COPD patients, enabling improved accuracy of noninvasive assessment of gas exchange inefficiency during incremental exercise testing.